764. Correlates of Lost to Follow-up Among Newly Diagnosed Older People with HIV in Ukraine. (31st December 2020) - Allen, Amy J; Zeziulin, Oleksandr; Postnov, Oleksandr; Rozanova, Julia; Litz, Taylor; Zaviryukha, Irina; Kiriazova, Tetiana; Shenoi, Sheela
Abstract: Background: Ukraine has the second largest HIV epidemic in Eastern Europe and Central Asia. Older People with HIV (OPWH) are at increased risk of poor outcomes compared to younger patients. We examined the prevalence and correlates of loss to follow-up (LTFU) among newly diagnosed patients in Ukraine. Methods: Retrospective chart review was conducted of 400 patients newly diagnosed with HIV July 1, 2017 - Dec 1, 2018. Data was collected from clinics in the city of Odessa and surrounding regions. OPWH were ≥50 years old at diagnosis and LTFU was defined as no contact with the HIV clinic for 90 days. Demographic, clinical characteristics, and follow-up outcomes were examined, and multivariate logistic regression was used to estimate the adjusted odds ratios at 95% confidence intervals. Results: Of the 400 people living with HIV, median age was 50 (IQR35-55), 196 (49%) were women, and 177 (44%) had CD4< 200cell/mm3 at diagnosis. Overall, 65 (16.5%) were LTFU from diagnosis and 54/65 (83%) were lost after their first appointment at the HIV clinic. Among those lost to follow-up, 49 (75%) were ≥50 at the time of diagnosis. Multivariate analysis showed LTFU was associated with age >50years (aOR 3.6, CI 1.8-7.3, p=0.001), lack of ART prescription (aOR 16.4, CI 8.5-31.8, p= 0.001), and living outside the city of Odessa (aOR 2.9, CI 1.5-5.7, p=0.002). Figure 1 shows the breakdown of lost to follow-up for OPWH. Figure 1. Retainment in HIV Care for OPWH compared to those <50 years old. Conclusion: LTFU among OPWH is significantly greater than younger people with HIV, and associated with lack of ART and living in nonurban settings. OPWH may benefit from differentiated HIV service delivery to reduce loss to follow up and interventions tailored to improving HIV outcomes for OPWH in resource-limited settings are urgently needed. Disclosures: All Authors : No reported disclosures